'All mouth and no trousers?' How many Conservative Party members voted for UKIP in 2015 – and why did they do so?. (November 2017) - Webb, Paul; Bale, Tim; Poletti, Monica
A survey of ordinary members of the United Kingdom's Conservative Party carried out in 2013 revealed that nearly 30% of them would seriously consider voting for the country's radical right wing populist party (United Kingdom Independence Party (UKIP)). However, we show that at the general election in 2015, only a very small proportion of them – around 5% of Tory grassroots members – actually did so, driven it seems mainly by alienation from the leadership and David Cameron in particular, as well as, perhaps, by concerns about the Conservative-led government's austerity policies. However, those party members who did eventually vote for UKIP were still much more likely to have expressed a propensity to vote for it in 2013 than those who did not. Since the Conservative Party has not experienced the same increase in membership as some of its competitors, and since members are an important part of parties' electoral campaigning, they should avoid alienating those members they do have – something of which Theresa May appears to be aware.